Attitudes of preschool teachers towards the importance of developing competences in natural sciences in working with children of the preschool age - Miljana D. Stajin; Zorica S. Kovačević (Inovacije u Nastavi, 2023)
In the modern society of science and technology, scientific literacy is viewed as one of the key educational competencies. However, research shows that young people’s interest in natural sciences is very low, that the average achievement of our 15-year-olds in the field of natural sciences is significantly lower compared to the OECD average, but also that significantly higher results in the field of natural sciences are achieved by our fourth-grade pupils who were included in the preschool education program. The paper presents the results of the research aimed at examining preschool teachers’ attitudes towards natural sciences and the development of scientific competencies in preschool children. The research goal defined in this way was operationalized in the following research tasks: 1) examine how preschool teachers assess their interest in natural sciences and their knowledge in the field of natural sciences 2) examine how preschool teachers assess children’s interest in the phenomena from the field of natural sciences, 3) examine what they perceive as the greatest contribution from situations during which they explore together with children the phenomena that are the subject of natural sciences. A descriptive method was used, with surveying and scaling as research techniques. The research results showed that preschool teachers have a positive attitude towards natural sciences, that they highly value children’s interest in natural sciences, that they view as the greatest contribution of situations during which children explore the phenomena studied in natural sciences in that they enable children to enjoy themselves and be happy, while the smallest contribution of these situations is perceived in developing children’s interest in science. Such research results show that preschool teachers have a positive attitude towards the development of scientific competences, but that they need stronger support in understanding the essential importance of the development of scientific competences in working with children.